Understanding E-bike Purchase Intentions: A Model of Environmental and Technological Determinants (Journal of Social Sciences Review, 2025)
The escalating need for sustainable urban mobility solutions amid concerns over climate change and fuel emissions makes the adoption of E-Bikes a critical area of study. This research investigates the psychological and cognitive factors that drive consumer Intention to Purchase E-Bikes (IPTEB), specifically examining how Environmental Awareness (EA), Consumer STEM Literacy (SL), and Perceived Technological Innovativeness (PTI) influence the perception of functional utility, operationalized as Perceived Technical Benefits (PTB). A quantitative study employing a cross-sectional design utilized Structural Equation Modeling (PLS-SEM) on data collected from 273 prospective E-Bike consumers in Multan, Pakistan. The structural model demonstrated high predictive power, explaining over 67% of the variance in the key endogenous constructs. All four hypothesized paths were supported, confirming that PTB is the overwhelming predictor of IPTEB (β= 0.820). Crucially, the antecedent variables influencing PTB ranked as follows: PTI (β= 0.373) was the strongest, closely followed by SL (β= 0.319), with EA exerting the weakest influence (β= 0.207). These findings suggest that while environmental concern provides motivation, the purchasing decision is fundamentally driven by rational, technology-based evaluations of product superiority, necessitating that manufacturers shift marketing strategy to focus on technical education and functional performance to maximize perceived value and accelerate adoption.
Keywords: STEM Literacy; Environmental Awareness; Perceived Technical Benefits; E Bikes